Online hospital appointment card with QR Code / Nabilatulwidad Abdul Mueiz and Mahfudzah Othman - Abdul Mueiz, Nabilatulwidad; Othman, Mahfudzah (College of Computing, Informatics and Media, UiTM Perlis, 2023)
New technologies have emerged in the contemporary world, and as time goes on, individuals will need to adjust to the changes brought about by those technologies. People who are familiar with technology could be intrigued by developments like web apps. Since the Covid-19 pandemic, people who have many obligations and little time to go to the government hospital to receive an appointment, such as employees and students, prefer online platforms. The creation of an Online Hospital Appointment Card with QR Code employing web-based tools like PHP, HTML, and MySQL will be described in this proposal. The planning, analysis, design, implementation, testing, and documentation phases of the system's development have all been implemented using the Waterfall model as the approach. Additionally, the system will use QR Code technology, which will provide a virtual appointment card. Patients will benefit from the QR Codes created by the system since they will provide a virtual appointment card, eliminating the need for patients to carry a physical card with them every time they have an appointment. Only their smartphone must be brought.